Somalia : First Review Under the Staff-Monitored Program-Press Release; and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2019)
This first review under the Staff-Monitored Program (SMP) of Somalia highlights that supported by a favorable rainy season, economic growth is recovering and inflation easing. However, unemployment is very high, and development and social needs are very large. Policy discussions centered on the 2018 supplementary budget, the 2019 budget, as well as the macroeconomic framework. Discussions also laid the groundwork for the second and final review under SMP III and on near-term policy priorities. All end-June and end-September 2018 indicative targets and all structural benchmarks (SBs) have been met. Of the 10 remaining SBs, due end-December 2018 and end-March 2019, preliminary information suggests that two have already been met, progress has been made towards achieving seven others, but completion of one SB is likely to be delayed. Considering satisfactory performance under the SMP and the authorities' continued strong commitment to reform implementation, the IMF staff supports the completion of the first review under SMP III. Risks to the program and the outlook remain elevated; however, a continued commitment to reform and donors' sustained support will help mitigate the risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet